Study of mutagenic effects with predicted carcinogenicity of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazole-3-yl)methyl)morpholine for further research in order to create a new drug with antifungal activity - I. V. Bushuieva; K. V. Petrova; B. P. Kyrychko; V. V. Parchenko (Zaporozhye State Medical University, 2022)
The development of effective and safe therapeutic agents using 1,2,4-triazole derivatives is gaining momentum in today's conditions. The value of such drugs is determined by the rapid and prolonged biological action, which is not accompanied by abrupt changes in homeostasis and pronounced side effects, which are characteristic of most pharmacological drugs of synthetic origin. In the context of a limited range of domestic antimicrobial and antifungal veterinary drugs on the national pharmaceutical market, one of the directions for solving this problem is the search, study, research, and development of drugs with antimicrobial and antifungal activity. The aim of this work was to study the mutagenic effects with the prediction of carcinogenicity of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazole-3-yl)methyl)morpholine with the prospect of further creation of new dosage forms for the treatment fungal pathologies of the skin. Materials and methods. Staph was used to study the effect of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazol-3-yl)methyl)morpholine in vitro Staphylococcus aureus, strain 209, its UV-2, UV-3 mutants and primary cell cultures. Accounting for gene mutations of microorganisms in the system of metabolic activation (Ames test) was carried out according to the method of L. M. Fonshtein in accordance with the requirements of "Methodological recommendations for assessing the mutagenic properties of new medicinal products" (Kyiv, 1996), supplemented by the methodology according to the recommendations of "Preclinical research of veterinary medicinal products" (edited by I. Ya. Kotsiumbas). Results. The results of studying the activity of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazole-3-yl)methyl)morpholine on a model of culture of tumor ascetic cells showed that at concentrations of 1.4 mg/ml, 0.8 mg/ml, 0.3 mg/ml, 0.015 mg/ml it was led to the regression of tumor cells of Ehrlich's carcinoma and C-37 sarcoma. In experiments with the Nk/L y strain, the same concentrations of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazole-3-yl)methyl)morpholine significantly slowed down cell growth. The results of the studies indicate a pronounced cytogenetic effect of thiophosfamide and sarcolysin, which suggests their metabolic activation in the body, as evidenced by a pronounced aberration of chromosomes. When comparing the cytogenetic effect of equimolar concentrations, the absence of cytogenetic activity of 4-((5-decylthio)-4-methyl-4-H-1,2,4-triazole-3-yl)methyl)morpholine was revealed. Conclusions. The positive results of studying the specific activity of 4-((5-decylthio)-4-methyl-4-Н-1,2,4-triazole-3-yl)methyl)morpholine in experiments in vitro were obtained which indicates the expediency of its extensive study in experimental animal tumors. In addition, according to these studies, no mutagenic effect was found at the doses that were used to predict carcinogenicity. Thus, it can be concluded that there is no cytogenetic effect.